PERBAIKAN SANITASI DAN HIGIENITAS DI SEKITAR KANDANG DARI PENGARUH URINE KAMBING MELALUI FILTRASI DAN FERMENTASI - SUGITHA, I MADE (Buletin Udayana Mengabdi; Vol 13 No 1 (2014): Vol 13, No 1, April 2014, 2014)
Bongancina has been known as the village of dairy goats. However, since last few years this potential has decreased to the present dairy goat production. This is because the experienced animals pain become ill during goat milking processes. The purpose of this Community service performed to provide knowledge Kelompok Tani Satwa Sari Ramban on the importance of sanitation to ensure hygiene during the milking processes. The methods of activity were demonstrating a good sanitation by improving the condition of the cage shaped by making a slanting floor (slope ± 50 degrees) equipped shelters urine. The results of the activities are that the participants have knowledge about simulating the sloping floor techniques equipped with shelters urine and were also trained in techniques biofermentasi urine. The conclusion of this activity is that the participants were very positive response and hope that events like this can be improved. Keywords : sanitation, urine, fermentation